Pemetaan Kerawanan serta Penentuan Prioritas Penanganan Penyakit Tuberkulosis di Provinsi Jawa Barat Tahun 2021 - Novitasari, Prihatini Dini; Inggarputri, Yuanita Rizky (Varians Jurnal Kesehatan Masyarakat, 2023)
Tuberculosis (TBC) is one of several communicable diseases which is still being public health problem in the world and in Indonesia. In 2021, West Java Province is still the province with the highest number of tuberculosis cases in Indonesia. The high cases of tuberculosis cannot be separated from various risk factors that are still frequently encountered in the community. This study aims to describe the distribution of tuberculosis cases in West Java and determine priority areas for tuberculosis treatment based on spatial/regional risk factors. This research was conducted in West Java Province in 2022, carried out descriptively using the Geographic Information System (GIS) application with a scoring technique. The research data is in the form of secondary data that comes from several open data access units of analysis based on regency/city administration. The results showed that out of 27 regencies/cities, there were 5 regencies/cities with very high levels of vulnerability with the first treatment priority being Bandung City, onwards Purwakarta Regency, Cianjur Regency, Bandung Regency, West Bandung Regency. The government is expected to be able to improve efforts to prevent and handle tuberculosis cases by prioritizing districts/cities with very high levels of vulnerability.